First Total Synthesis of Jomthonic Acid A - Dumpala, Mohan; Srinivas, Batthula; Radha Krishna, Palakodety (Synlett, 2020)
A stereoselective total synthesis of jomthonic acid A is described. The key features of the synthetic strategy are a Sharpless asymmetric epoxidation, a Gilmann reagent-induced methylation, a Mitsunobu reaction, a Yamaguchi esterification, and an O-(benzotriazol-1-yl)-N,N,N′,N′-tetramethyluronium tetrafluoroborate (TBTU)-mediated amide coupling. Jomthonic acid A is an architecturally rare amino acid containing a β-methylphenylalanine residue and a 4-methyl-(2E,4E)-hexa-2,4-dienoate moiety. It shows antidiabetic and antiatherogenic activities when tested against mouse ST-13 preadiopocytes.
Keywords: Gilmann reaction; Mitsunobu reaction; Yamaguchi esterification; amide coupling; total synthesis; jomthonic acid A